Exploring malay personality structure using a combined EMIC-ETIC approach - Jusmawati Fauzaman (2015)
This lexical-based study explores the Malay adjectives personality factor structure. The structure of the Malay personality lexicon was investigated using self-ratings (N=589) on a total set of 261 personality-descriptors. Personality-related descriptors were extracted from a Malay dictionary via comprehensive sampling and subjected to frequency of use ratings. Descriptors were classified into Person Descriptive System and subjected to PCA analysis on three different variable selection templates - Disposition, Disposition and Temporary Condition, and Inclusive. The hierarchical emergence of factors from 1 to 8 was explored. Substantive mode of factor content comparison was adopted. The Malay adjective factor structure displayed robust factor formations only in the non-ipsatized rather than the ipsatized datasets at the three-, five-, and six-factor solutions. Three-factor solution displayed a robust but broad Big-Three factor formation in the non-ipsatized Disposition and Temporary Condition template. The robustness of the Big-Five factor structure was found in the Malay adjective lexicon at the five-factor solution, differing in its structure formation due to different templates. A replicable Big-Five factor structure was found in the non-ipsatized Disposition template while the non-ipsatized Disposition and Temporary Position as well as the Inclusive templates displayed a rotational variant of the Big-Five factor structure with clear emergence of two Agreeableness factors. A Big-Six factor structure was retrieved at the six-factor solution in the non-ipsatized inclusive template. The universality of the Big-Three, the classic as well as the rotational variant of Big-Five, and Big-Six was relatively confirmed in another non-Indo European language, the Malay language of the Austronesian language family.